2011
DOI: 10.1016/j.atmosenv.2011.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene and monoterpene emissions from a mixed temperate forest

Abstract: Isoprene (IP) and monoterpenes (MTP) are the most abundant biogenic volatile organic compounds (BVOCs) emitted by terrestrial vegetation, particularly by forests. Global IP and MTP emissions are estimated to be 460 TgC yr −1 and 117 TgC yr −1 , respectively, representing 80% of the total BVOC emissions. These components have a significant impact on atmospheric chemistry and physics.Long term ecosystem-scale BVOC flux measurement is the sole method allowing quantification and description of BVOC emission respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 79 publications
4
29
1
Order By: Relevance
“…The compounds were further diluted (2-12 ppbv range) using a dynamic dilution system. More details can be found in Laffineur et al (2011).…”
Section: Instrumentation and Bvoc Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…The compounds were further diluted (2-12 ppbv range) using a dynamic dilution system. More details can be found in Laffineur et al (2011).…”
Section: Instrumentation and Bvoc Samplingmentioning
confidence: 99%
“…The filtering suppresses also data points outside the factory direction but in a small number of cases in comparison with the number of data point that succeed the test. This procedure was described in detail by Laffineur et al (2011).…”
Section: Data Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghirardo et al (2010) used stable isotope labelling on Norway spruce (Picea abies) and Scots pine and observed that the approximate contribution of de novo MT emissions could range between 25 and 45 % for spruce and 40 and 70 % for pine. Since it has been shown that light-dependent and light-independent emissions happen simultaneously, it has been suggested that the observed MT emission patterns should be regarded as a combination of light-dependent and light-independent emissions instead of only being light-independent for some species (Ghirardo et al, 2010;Taipale et al, 2011;Laffineur et al, 2011;Staudt and Lhoutellier, 2011;Song et al, 2014).…”
Section: Y Van Meeningen Et Al: Isoprenoid Emission Response To Chamentioning
confidence: 99%
“…Since PTR-MS determines only the mass of the product ions, it is impossible to distinguish between different VOCs within the same mass. The signal at 137 m/z is attributed to the total mixing ratio of MT compounds (Laffineur et al, 2011). The performance of DEHM with respect to the MT mixing ratios is evaluated according to the correlation coefficient and the fractional bias in Tables 1 and 2.…”
Section: Simulation Of Monoterpenes From Vegetationmentioning
confidence: 99%